Trees diversity in Mt. Naghut, Maydolong, Eastern Samar, Philippines - Forteza, Darlene T.; Ladiao, Facundo Rey Montes; Laureano, Venus Zenia Saliling; Muncada, Myra Loquinte; Vilbar, Roramie Roa
A survey conducted in Mt. Naghut, Maydolong, Eastern Samar from November 1998 to March of 1999 revealed 51 species of trees belonging to 21 families and 34 genera. Species diversity value is 1.5334 suggesting a highly diverse ecosystem, while dominance index reached a value of 0.0394. Similarity indices among the sampling stations is high between Stations No. 2 and 3 with a value of 0.3736 and least between Stations 1 and 6 with only 0.1017, which suggests a distinct zonation in the distribution of the different species. Whereas, species distribution and abundance is considered high with about 8.7 species per 500 square meters. This forest may be classified as a dipterocarp forest because of the dominance of the Family Dipterocarpaceae, as well as a mossy forest, as the genus Lithocarpus is common to all sampling stations It is also a mature forest considering that 84.62% of the tree species attained an average diameter at breast height (dbh) of 73.1 centimeters.